2008
DOI: 10.1177/0022466907313346
|View full text |Cite
|
Sign up to set email alerts
|

Using Cultural and Social Capital to Improve Postsecondary Outcomes and Expand Transition Models for Youth With Disabilities

Abstract: The terms cultural and social capital, conceptualized by education philosopher and researcher Pierre Bourdieu, play an important role in the lives of youth with disabilities during transition into adulthood. Although research, legislation, and practice acknowledge the importance of resources that are established via social networks, insufficient attention has been dedicated to the forms of capital possessed by young adults with disabilities or to teachers' expectations of the role of capital in achieving posts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
92
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(94 citation statements)
references
References 49 publications
0
92
0
2
Order By: Relevance
“…This review of evidence-based practices for transition also found that there is a need for research that focuses on specific sub-populations of students and to include that information in the findings (Trainor, 2008). Without this disaggregated information, it is difficult to determine whether these evidence-based practices are effective in improving postschool outcomes for students who are Black and have disabilities or whether different approaches are needed to address differing challenges for this population.…”
Section: Introductionmentioning
confidence: 99%
“…This review of evidence-based practices for transition also found that there is a need for research that focuses on specific sub-populations of students and to include that information in the findings (Trainor, 2008). Without this disaggregated information, it is difficult to determine whether these evidence-based practices are effective in improving postschool outcomes for students who are Black and have disabilities or whether different approaches are needed to address differing challenges for this population.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, this type of networking increases the likelihood that CLD families will develop the social and cultural capital necessary for success when they are linked with other families who are more familiar with the dominant culture. Support for this statement comes from Trainor (2008), who indicated that sound transition planning and instructional practices require careful consideration of the cultural and social capital that adolescents with disabilities bring to the transition process. Family-to-family networks allow for the creation, acquisition, and use of capital during transition into adulthood thereby providing sociocultural information regarding services for youth with disabilities.…”
Section: Sustainable Transition Planningmentioning
confidence: 99%
“…Constituye un proceso encaminado a lograr objetivos relacionados con la participación en actividades formativas más allá de la educación obligatoria, la inclusión laboral, el inicio de la emancipación de la familia, la implicación y participación activa en distintos espacios de la comunidad, y la posibilidad de experimentar relaciones sociales y personales satisfactorias (Cobb y Alwell, 2009; Kaehne y Beyer, 2009; Martínez Rueda, 2002;Test et al, 2009;Trainor, 2008). Las trayectorias individuales de transición que llevan a conseguir estos objetivos se construyen fundamentalmente en base a la articulación de apoyos que se ofrecen en servicios escolares y postescolares.…”
Section: La Transición a La Vida Adulta De Las Personas Con Discapaciunclassified